The Empire of Amir Timur and His Political Successors: Kipchaks in Social and Administrative Structures - Rustam A. Abdumanapov (Oriental Studies)
Introduction. Insights into the Kipchak ethnic component of Central Asian history are a very important field instrumental in reconstructing actual processes across the vast Eurasian territories. The component has been studied within diverse ethnic and national histories of the region but the impact of Kipchak tribes in the history of the Timurid Empire and its successor states remains as uninvestigated. Goals. The paper analyzes a variety of sources to delineate the place of Kipchak tribes in social and administrative structures of Amir Timur’s empire and domains of his descendants. Materials and methods. The article examines The Life of [Sultan] Jalal al-Din Mangburni by Shihab al-Din Muhammad al-Nasawi, The Chronicles of Amir Timur’ Invasion of India by Ghiyas-ud-din Ali, The Rise of the Two Auspicious Constellations and the Confluence of the Two Oceans by Abd-al-Razzāq Samarqandī, The Book of Victories by Nizam al-Din Shami, The Book of Victories by Sharaf ad-Din Ali Yazdi, The Glorifier of Genealogies, Tarikh-i Rashidi by Mirza Muhammad Haidar, Babur-nama by Zahiru’d-din Muhammad Babur, Miracles of Fate in the History of Timur by Ahmed ibn Arabshah, Ming Shilu (Ming Veritable Records), etc. Our analysis of such various sources based on the principle of historicism with the aid of special historical methods concludes as to the degree of Kipchaks’ participation in political and administrative structures of the mentioned states. Conclusions. The considered sources attest to representatives of Kipchak tribes were close enough to associates of Amir Timur and would hold high positions, acting as emirs of diwans, tuvachis, emirs of tumens, seal keepers, etc. There were several groups of Kipchaks — ones in the Ilchikdai Ulus, Kipchaks associated with Jalairs, separate communities ruled by various emirs. The Timurid era witnessed the shaping and rise of several Kipchak clans that served as executives in the states of Amir Timur and his descendants.